Short and long term efficiencies of debris risk reduction measures: Application to a European LEO mission. Issue 1 (1st January 2015) - Lang, T.; Kervarc, R.; Bertrand, S.; Carle, P.; Donath, T.; Destefanis, R.; Grassi, L.; Tiboldo, F.; Schäfer, F.; Kempf, S.; Gelhaus, J.
Abstract: Recent numerical studies indicate that the low Earth orbit (LEO) debris environment has reached a point such that even if no further space launches were conducted, the Earth satellite population would remain relatively constant for only the next 50 years or so. Beyond that, the debris population would begin to increase noticeably, due to the production of collisional debris (Liou and Johnson, 2008 ). Measures to be enforced play thus a major role to preserve an acceptable space mission risk and ensure sustainable space activities. The identification of such measures and the quantification of their efficiency over time for LEO missions is of prime concern in the decision-making process, as it has been investigated for the last few decades by the Inter-Agency Space Debris Coordination Committee (IADC). This paper addresses the final results of a generic methodology and the characteristics of a tool developed to assess the efficiency of the risk reduction measures identified for the Sentinel-1 (S1) mission. This work is performed as part of the 34-month P 2 -ROTECT project (Prediction, Protection & Reduction of OrbiTal Exposure to Collision Threats), funded by the European Union within the Seventh Framework Programme. Three ways of risk reduction have been investigated, both in short and long-term, namely: better satellite protection, better conjunction prediction, and cleaner environment. According to our assumptions, the S1 mission vulnerability evaluations in the long term (from 2093 to 2100) show that full compliance to the mitigation measures leads to a situation twice safer than that induced by an active debris removal of 5 objects per year in a MASTER 2009 Business-As-Usual context. Because these measures have visible risk reduction effects in the long term, complementary measures with short response time are also studied. In the short term (from 2013 to 2020), a better prediction of the conjunctions is more efficient than protecting the satellite S1 itself. By combining a better prediction with an enhanced satellite protection the S1 is estimated to extend its extra mission lifetime by 4% with respect to its nominal lifetime (7.25 years).